Environmental Controls on the Riverine Export of Dissolved Black Carbon. Issue 7 (18th July 2019) - Jones, Matthew W.; de Aragão, Luiz E. O. C.; Dittmar, Thorsten; de Rezende, Carlos E.; Almeida, Marcelo G.; Johnson, Ben T.; Marques, Jomar S. J.; Niggemann, Jutta; Rangel, Thiago P.; Quine, Timothy A.
Abstract: Each year, tropical rivers export a dissolved organic carbon (DOC) flux to the global oceans that is equivalent to 4% of the global land sink for atmospheric CO2 . Among the most refractory fractions of terrigenous DOC is dissolved black carbon (DBC), which constitutes 10% of the total DOC flux and derives from the charcoal and soot (aerosol) produced during biomass burning and fossil fuel combustion. Black carbon (BC) has disproportionate storage potential in oceanic pools and so its export has implications for the fate and residence time of terrigenous organic carbon (OC). In contrast to bulk DOC, there is limited knowledge of the environmental factors that control riverine fluxes of DBC. We thus completed a comprehensive assessment of the factors controlling DBC export in tropical rivers with catchments distributed across environmental gradients of hydrology, topography, climate, and soil properties. Generalized linear models explained 70 and 64% of the observed variance in DOC and DBC concentrations, respectively. DOC and DBC concentrations displayed coupled responses to the dominant factors controlling their riverine export (soil moisture, catchment slope, and catchment stocks of OC or BC, respectively) but varied divergently across gradients of temperature and soil properties. DBC concentrations also varied strongly with aerosol BC deposition rate, indicating further potential for deviation of DBC fluxes from those of DOC due to secondary inputs of DBC from this unmatched source. Overall, this study identifies the specific drivers of BC dynamics in river catchments and fundamentally enhances our understanding of refractory DOC export to the global oceans. Key Points: Common hydrological factors explain variability in riverine dissolved organic carbon and dissolved black carbon concentrations, however; Variation in soil properties, temperature, antecedent rainfall, and aerosol deposition may drive divergence in their relative abundance At an unprecedented geographic scale, we find that aerosol BC contributes significantly to riverine fluxes of DBC